The Application of Artificial Intelligence Technology for the Diagnosis of Malignant Tumors: A Review - Chauhan, Kavita; Singal, Kabir; Agarwal, Anshoo; Sherazi, Zainiya; Syed, Asmara; Hussain Shah, Syed Sajid; Kauser, Fariha; Younas, Madiha (Journal of Neonatal Surgery, 2025)
Background: The digital technology has revolutionized many fields including the healthcare. The advancement in digital technology in the form of artificial intelligence is going to revamp the patient care in near future. The application of convolutional neural network in the computer aided diagnostic system has revealed very promising results. Material and methods: The research papers were collected after searching the databases by using the specific key words such as convolutional network (CNN), ResNet34, ResNet50, ResNet101, ResNet152, EfficientNet B3 and VGG-19. The search period was five years from 2020 to 2024. Results: A total of 33 research article have been selected for this review paper on the basis of inclusion and exclusion criteria. The significant majority of the studies revealed that diagnostic accuracy of artificial intelligence technology regarding the histopathological diagnosis of malignant tumors ranged from 85% to 100%. Discussion: The computer aided diagnostic system based on artificial intelligence technology has emerged as excellent technique for the histopathological examination of the tissue specimens. In some conditions, it has surpassed the pathologist in the speedy evaluation of lesions with more diagnostic accuracy. Conclusion: The application of artificial intelligence for the diagnosis of the malignant tumors could provide a very valuable assistance to the pathologist. It would provide more speedy results with high accuracy which could be very important in the patient care